An investigation into capital budgeting decisions: a case of Wadoma Royale Hotel in Ashanti Region - Gbadago, Frank Y. (2011)
A long essay submitted to KNUST- School of Business, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of Master of Business Administration.